InterPARES 2 and the Records-Related Legislation of the European Union - Foscarini, Fiorella (Archivaria, 2007)
This article provides an overview of European Union legislation, policy, and regulations relating to the requirements for the preservation of digital records. It also serves as a window into one line of inquiry being undertaken in the InterPARES 2 project, that is, the study of the barriers and enablers to the preservation of digital records that may be found in the enabling legislation of a number of countries all over the world, including the European Union as a supranational entity. RÉSUMÉ Ce texte fournit un aperçu de la législation, des politiques et des règlements de l’Union européenne par rapport aux exigences pour la préservation des documents numériques. Il sert aussi comme point d’entrée à un champ d’enquête sur lequel le projet InterPARES 2 s’est penché, c’est-à-dire l’étude des barrières et des outils pour la préservation des documents numériques qui peuvent se trouver dans la législation de bon nombre de pays dans le monde, y inclus l’Union européenne en tant qu’entité supra-nationale.